Intensive vs Standard Blood Pressure Control in Adults 80 Years or Older: A Secondary Analysis of the Systolic Blood Pressure Intervention Trial. Issue 3 (16th December 2019) - Pajewski, Nicholas M.; Berlowitz, Dan R.; Bress, Adam P.; Callahan, Kathryn E.; Cheung, Alfred K.; Fine, Larry J.; Gaussoin, Sarah A.; Johnson, Karen C.; King, Jordan; Kitzman, Dalane W.; Kostis, John B.; Lerner, Alan J.; et al.
Abstract : OBJECTIVES: To evaluate the effect of intensive systolic blood pressure (SBP) control in older adults with hypertension, considering cognitive and physical function. DESIGN: Secondary analysis. SETTING: Systolic Blood Pressure Intervention Trial (SPRINT) PARTICIPANTS: Adults 80 years or older. INTERVENTION: Participants with hypertension but without diabetes (N = 1167) were randomized to an SBP target below 120 mm Hg (intensive treatment) vs a target below 140 mm Hg (standard treatment). MEASUREMENTS: We measured the incidence of cardiovascular disease (CVD), mortality, changes in renal function, mild cognitive impairment (MCI), probable dementia, and serious adverse events. Gait speed was assessed via a 4‐m walk test, and the Montreal Cognitive Assessment (MoCA) was used to quantify baseline cognitive function. RESULTS: Intensive treatment led to significant reductions in cardiovascular events (hazard ratio [HR] = .66; 95% confidence interval [CI] = .49‐.90), mortality (HR = .67; 95% CI = .48‐.93), and MCI (HR = .70; 95% CI = .51‐.96). There was a significant interaction ( P  < .001) whereby participants with higher baseline scores on the MoCA derived strong benefit from intensive treatment for a composite of CVD and mortality (HR = .40; 95% CI = .28‐.57), with no appreciable benefit in participants with lower scores on the MoCA (HR = 1.33 = 95% CI = .87‐2.03). There was no evidence of heterogeneity of treatment effects with respect to gait speed. Rates of acute kidney injury and declines of at least 30% in estimated glomerular filtration rate were increased in the intensive treatment group with no between‐group differences in the rate of injurious falls. CONCLUSION: In adults aged 80 years or older, intensive SBP control lowers the risk of major cardiovascular events, MCI, and death, with increased risk of changes to kidney function. The cardiovascular and mortality benefits of intensive SBP control may not extend to older adults with lower baseline cognitive function. Trial Registration: Clinicaltrials.gov identifier: NCT01206062. J Am Geriatr Soc 68:496–504, 2020